2011
DOI: 10.5194/acp-11-201-2011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deep convection in the tropical tropopause layer in West Africa: in-situ observations and mesoscale modelling

Abstract: Abstract. We present the analysis of the impact of convection on the composition of the tropical tropopause layer region (TTL) in West-Africa during the AMMA-SCOUT campaign. Geophysica M55 aircraft observations of water vapor, ozone, aerosol and CO 2 during August 2006 show perturbed values at altitudes ranging from 14 km to 17 km (above the main convective outflow) and satellite data indicates that air detrainment is likely to have originated from convective cloud east of the flights. Simulations of the BO-LA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
4
19
0
Order By: Relevance
“…For the SCOUT-AMMA study in the lower panel the SO 2 source contributions were located in East Africa and East India/South-East Asia. The latter is in qualitative agreement with the calculations by , who showed that ∼40 % of the air masses in the mid-TTL over West Africa during SCOUT-AMMA were influenced by injection of lower tropospheric air from Asia and India, while Fierli et al (2011) concluded that over Africa regional deep convection played a role as well. In Fig.…”
Section: Transport Model Calculations and Estimation Of So 2 Loadingssupporting
confidence: 80%
See 3 more Smart Citations
“…For the SCOUT-AMMA study in the lower panel the SO 2 source contributions were located in East Africa and East India/South-East Asia. The latter is in qualitative agreement with the calculations by , who showed that ∼40 % of the air masses in the mid-TTL over West Africa during SCOUT-AMMA were influenced by injection of lower tropospheric air from Asia and India, while Fierli et al (2011) concluded that over Africa regional deep convection played a role as well. In Fig.…”
Section: Transport Model Calculations and Estimation Of So 2 Loadingssupporting
confidence: 80%
“…Finally, a new approach to the region above the same MCS was performed before the Geophysica turned back to the mission base. The level of main outflow of this MCS was located at the 353 K level according to Fierli et al (2011). These authors investigate the convective uplift of air masses due to this particular MCS and find highly variable convective ages from a few up to 48 h.…”
Section: Case Studies Of Three Npf Events Over South America and Overmentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds well with observations carried out during the AMMA (African Monsoon Multidisciplinary Analyses) campaign during July and August 2006. Aircraft based measurements of several gas species were used to show the main convective outflow to be around 200 hPa in this region, and on certain days up to 100 hPa Fierli et al, 2011). Satellite based measurements of CO during the same time period show a convective influence up to around 220 hPa, with CO distributions above 150 hPa being controlled by large-scale transport (Barret et al, 2008).…”
Section: Location Of Convectionmentioning
confidence: 99%